2015
DOI: 10.1016/j.envres.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Indoor particulate matter in rural, wood stove heated homes

Abstract: Ambient particulate matter (PM) exposures have adverse impacts on public health, but research evaluating indoor PM concentrations in rural homes in the United States using wood as fuel for heating is limited. Our objectives were to characterize indoor PM mass and particle number concentrations (PNCs), quantify infiltration of outdoor PM into the indoor environment, and investigate potential predictors of concentrations and infiltration in 96 homes in the northwestern US and Alaska using wood stoves as the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…A range from 6 µg·m −3 to 55 µg·m −3 was documented by these authors. A study in 50 homes (Montana, USA) [40] with wood stoves reported PM 2.5 concentrations of 32.3 ± 32.6 µg·m −3 (ranging from to 6.0 µg·m −3 to 163 µg·m −3 ) for a sampling period of 48 h. Results in the same range were obtained in a study in 96 homes (USA) [41] where, for two sampling periods, the mean daily concentrations of 28.8 ± 28.5 µg·m −3 and 29.1 ± 30.1 µg·m −3 were observed. When comparing particulate matter levels in living rooms of houses with central heating or wood heating [42], PM 10 levels were found to be six times higher in houses equipped with wood heating systems (203 ± 201 µg·m −3 ) than in dwellings with central heating.…”
Section: Combustion Conditions Open Fireplacesupporting
confidence: 68%
“…A range from 6 µg·m −3 to 55 µg·m −3 was documented by these authors. A study in 50 homes (Montana, USA) [40] with wood stoves reported PM 2.5 concentrations of 32.3 ± 32.6 µg·m −3 (ranging from to 6.0 µg·m −3 to 163 µg·m −3 ) for a sampling period of 48 h. Results in the same range were obtained in a study in 96 homes (USA) [41] where, for two sampling periods, the mean daily concentrations of 28.8 ± 28.5 µg·m −3 and 29.1 ± 30.1 µg·m −3 were observed. When comparing particulate matter levels in living rooms of houses with central heating or wood heating [42], PM 10 levels were found to be six times higher in houses equipped with wood heating systems (203 ± 201 µg·m −3 ) than in dwellings with central heating.…”
Section: Combustion Conditions Open Fireplacesupporting
confidence: 68%
“…Studies conducted in rural areas have shown that the use of wood and/or coal for cooking or heating can be a significant source of particulate matter inside homes [8,9]. PM 10 in homes that use biomass fuel was found to be 10-70 times above ambient concentrations observed in some of the world's most polluted cities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The varied PM2.5 response across homes in our studies and others may be due to factors (e.g. household size, household activities, ventilation) other than the introduction of a new woodstove [25,27]. The recent Asthma Randomized Trial of Indoor Wood Smoke study demonstrated that air filtration units were superior (68% decrease) to woodstove change-out (no significant reductions) in reducing PM2.5 in homes; however, their effectiveness in reducing LRTIs is unknown [28].…”
Section: Discussionmentioning
confidence: 99%